The state program’s improvement of health of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
This article discusses the state programs in the sector of health care in our country and how they are made. Through state programmes in the health sector reaching economic achievements, the people of the state changed its view on the health. Unified national health system considers questions of management in the health sector. As well as introducinga Unified national system of health held a series of work. This comparison of the normative-legal base, changes and additions to the legislative acts.
Keywords: the industry of health; the state programme; the republican budget; strategy; medical activities; the organization of health care.